2014
DOI: 10.1111/dme.12483
|View full text |Cite
|
Sign up to set email alerts
|

Increasing capacity to deliver diabetes self‐management education: results of the DESMOND lay educator non‐randomized controlled equivalence trial

Abstract: Diabetes education delivered jointly by a trained lay person and a healthcare professional educator with the same educator role can provide equivalent patient benefits. This could provide a method that increases capacity, maintains quality and is cost-effective, while increasing access to self-management education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
19
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 27 publications
3
19
0
Order By: Relevance
“…Illness coherence has previously been associated with a range of protective and preventive behaviours in many health settings (Carey et al, 2014;Figueiras & Alves, 2007;Tanenbaum et al, 2015;Van der Elst et al, 2015). The results of the present study extend on these works by indicating that holding a coherent understanding of cervical cancer is associated with both greater intention to be vaccinated, as well as having undergone vaccination.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Illness coherence has previously been associated with a range of protective and preventive behaviours in many health settings (Carey et al, 2014;Figueiras & Alves, 2007;Tanenbaum et al, 2015;Van der Elst et al, 2015). The results of the present study extend on these works by indicating that holding a coherent understanding of cervical cancer is associated with both greater intention to be vaccinated, as well as having undergone vaccination.…”
Section: Discussionsupporting
confidence: 81%
“…Within the clinical context of diabetes, another study further demonstrated improvements in patient illness coherence regarding diabetes self-management through a structured education programme that provided information about the Disease Risk-Action Link pertaining to blood glucose regulation and dietary and lifestyle factors (Carey et al, 2014). This study differed from Bishop et al (2005) and Hall et al (2004) in that participants received information about the advantages of adopting a health-enhancing behaviour, rather than the disadvantages of continuing a harmful behaviour.…”
mentioning
confidence: 99%
“…Our qualitative findings support the positive quantitative findings from the DESMOND Lay Educator study,10 which indicated that patients can derive equivalent benefits from education sessions involving one lay educator and one healthcare professional educator, compared with sessions delivered by two healthcare professional educators (box 1). The findings from our interviews with a range of stakeholders highlighted some concerns, but we identified positive overall perceptions regarding the acceptability of using lay educators.…”
Section: Discussionsupporting
confidence: 80%
“…The aim of the DESMOND Lay Educator study (box 1) was to address this gap in the literature.
Box 1 The Diabetes Education and Self Management for Ongoing and Newly Diagnosed (DESMOND) Lay Educator study10 Study design and timing: Non-randomised equivalence trial with a qualitative substudy, conducted between 2008 and 2011 (including development stage). Setting: Recruitment for the trial was through general practices (primary care centres) in four areas across England and Scotland. Intervention: Non-randomised participant allocation to a DESMOND course delivered in the standard format by two trained healthcare professional educators (control format) or by one formally recruited, trained lay educator and one professional educator (intervention format). Having diabetes was not a selection or exclusion criterion for recruitment of lay educators.
…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation